3D artistic mapping of the urban environment for tourism information support - German Anna (Polish Cartographical Review)
With the development of the tourism sphere, its information support is also developing, in particular, represented with cartographic works. One of the forms of cartographic support for tourism is three-dimensional artistic maps (3D-maps, panoramic maps) and cartographic web applications. By our understanding the panoramic map of the city is a cartographic image of the urban environment, made with regard to linear and aerial perspectives on the principle of artistic painting and created an illusory sense of volumetricity. Such maps illustrated the historical parts of cities, park zones, museums-estates, individual architectural monuments become popular souvenirs, but their handwritten creation is rather labor-intensive and requires high artistic skills.